Peningkatan kemantapan agregat tanah mineral oleh bakteri penghasil eksopolisakarida Aggregate stability improvement of mineral soil by exopolysaccharide-producing bacteria - Laksmita Prima SANTI; Ai DARIAH; Didiek Hadjar GOENADI (Menara Perkebunan, 2008)
Summary Pseudomonas fluorescens PG7II.1, Flavobacterium sp. PG7II.2, and  Pseudomonas diminuta PG7II.9 have a potential to produce exopolysaccharide which help the  formation and stabilization of soil aggregate. These bacteria have been isolated from the rhizosphere of Saccharum officinarum.  Exopolysaccharide production in ATCC 14 liquid medium with sucrose was higher than that obtained from glucose, lactose, and 4-hydroxyphenil acetic acid       (4-HAA) as a carbon sources. Producing of exopolysaccharide from these bacteria were 8.04 (P. fluorescens PG7II.1), 2.0 (Flavo-bacterium sp. PG7II.2) and 1.82 mg/mL (P. diminuta PG7II.9). Aggregate Stability Index (ASI) of mineral soil material was 114 when inoculated by these isolates after 60 days incubation period at ambient temperature. The ASI value of inoculated mineral soil material significantly different with uninoculated. The optimum of bacterial suspension to increase aggregate stability of mineral soil material was 12.5% (v/w) consisted of 109 CFU per mL.  Ringkasan          Pseudomonas fluorescens PG7II.1, Flavobacterium sp. PG7II.2, dan Pseudomonas diminuta PG7II.9, memiliki potensi dalam menghasilkan eksopolisakarida untuk pem-bentukan dan kemantapan agregat tanah. Ketiga bakteri tersebut diisolasi dari rhizosfer Saccharum officinarum. Sukrosa merupakan sumber karbon terbaik untuk produksi eksopolisakarida di dalam medium cair ATCC 14 apabila dibandingkan dengan glukosa, laktosa, dan 4-hydroxyphenil acetic acid  (4-HAA). Eksopolisakarida yang dihasilkan dari ketiga bakteri tersebut masing-masing 8,04 (P. fluorescens PG7II.1); 2,0 (Flavobacterium sp. PG7II.2) dan 1,82 mg/mL (P. diminuta PG7II.9). Inokulasi ketiga isolat tersebut ke dalam bahan tanah mineral memberikan indeks stabilitas agregat (ASI) sebesar 114 setelah 60 hari inkubasi pada suhu ruang. Nilai indeks ini berbeda secara nyata apabila dibandingkan dengan bahan tanah mineral tanpa inokulan. Jumlah suspensi bakteri yang diperlukan untuk meningkatkan nilai indeks stabilitas agregat di dalam bahan tanah mineral secara optimum ialah 12,5% (v/b), dengan jumlah populasi bakteri 109 CFU   per mL.